(untitled) (Journal of Applied Engineering Science, 2022)
Prof. Dr. Gradimir Danon, Editor in Chief of the Journal of Applied Engineering Science demanded the change in the Acknowledgement section of the paper. CLARIFICATION Upon the written remark of the corresponding author Mr. Doan Perdana from Telkom University, Faculty of Electrical Engineering, Bandung, Indonesia, the authors of the paper "Increasing the measurement of soil water content with the characterization of magnetic field induction sensors using model equations for the internet of things application" 20(2022)1, 913, 137-144, DOI: 10.5937/jaes0-30730 requested to add acknowledgement section to their paper. The acknowledgement has to be added as follows: “This work was supported by Skema Invitasi, LPDP, Kementrian Keuangan, 2020-2021, with Contract No. PRJ-56/LPDP/2020.” This addition does not affect the original paper.